The Effect of Application of Creative Problem Solving Learning Methods on Students' Mathematics Learning Outcomes - Dariah; Toto Syatori Nasehudin; Arif Muchyidin (MASI Mandiri Edukasi, 2022)
This study aims to determine: 1) Student responses after the application of the Creative Problem Solving learning method; 2) Students' mathematics learning outcomes after using the Creative Problem Solving learning method; 3) Whether or not there are differences and the influence of the application of the Creative Problem Solving learning method on students' mathematics learning outcomes. This research is an experimental type of research, namely research that is used to find the effect of specific treatments on others under controlled conditions. The experiment was carried out with the object of research consisting of the experimental and control classes. The researcher used class X IPS 1 as the experimental class, which consisted of 30 students, and class X IPS 2 as the control class, which consisted of 32 students. Sampling was done by random cluster sampling. The results showed that the student's response to applying the Creative Problem Solving learning method was reasonable based on the results of the questionnaire data recapitulation, which showed an average number of 77.39% and was in solid criteria. Student learning outcomes by applying the Creative Problem Solving learning method are included in the excellent category, with the average score obtained by the experimental class students of 88.50. There were 29 students out of 30 who scored above the KKM set by the school, which was 67. Meanwhile, the average score for the control class only reached 76.75. The results of the t-test show differences in student learning outcomes using the Creative Problem Solving learning method with those using ordinary or conventional learning methods with a correlation value of 0.404, which can be said to have a moderate effect